International Legal Aspects for Ensuring Phytosanitary Safety on the Example of the Analysis of the WTO Agreement on the Application of Sanitary and Phytosanitary Measures - RASHEVA, Gulnur K.; AIGARINOVA, Gulnar T.; AIDARKHANOVA, Kulyash N. (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).11, 2019)
Ensuring phytosanitary safety is one of the most important tasks of our time, which arose as a result of the growing processes of globalization and internationalization of legal systems and the world economy, as well as scientific and technological progress, which led to the fact that changes in one country have become a threat to other countries. The aim of this research is a comprehensive study of the international legal regulation of phytosanitary safety in the framework of the World Trade Organization, as well as its impact on the member countries of the organization and the legislation of the Republic of Kazakhstan. This scientific work examined the main provisions of the Marrakesh agreement establishing the World Trade Organization, implicitly relating to food safety and phytosanitary issues, the Agreement on the Application of Sanitary and Phytosanitary Measures of the WTO, as well as the prospects for the bringing of national legislation in accordance with the provisions of the SPS Agreement and its further application. In this research were considered scientific works and researches of many foreign, domestic and Russian scientists, as well as various manuals and brochures of the WTO. As a result, the scientific work identified the main advantages and disadvantages of the application of the SPS Agreement for both developed and developing countries. Also, it will allow to get acquainted in detail not only with the basic legal framework, but also with its impact on the legislation and activities of the Republic of Kazakhstan in the field of phytosanitary safety.